Management of ventricular arrhythmias in patients with LVAD. (May 2020) - Maradey, Joan A.; Singleton, Matthew J.; O'Neill, Thomas J.; Bhave, Prashant D.
Abstract : Purpose of review: Left ventricular assist devices (LVADs) have extended the life expectancy of patients with heart failure. The hemodynamic support afforded by LVADs in this population has also resulted in patients having prolonged ventricular arrhythmias. The purpose of this article is to review the mechanisms of ventricular arrhythmias in LVADs and the available management strategies. Recent findings: Recent evidence suggests that prolonged ventricular arrhythmias may result in increased mortality in patients with LVADs. Summary: Successful management of ventricular arrhythmias in patients with LVAD requires interdisciplinary collaboration between electrophysiology and heart failure specialists. Medical management, including changes to LVAD changes, heart failure medication management, and antiarrhythmics constitute the initial treatment for ventricular arrhythmias. Surgical or endocardial ablation are reasonable options if VAs are refractory.